Occupational exposure to arsenic and risk of nonmelanoma skin cancer in a multinational European study. Issue 9 (9th July 2013) - Surdu, Simona; Fitzgerald, Edward F.; Bloom, Michael S.; Boscoe, Francis P.; Carpenter, David O.; Haase, Richard F.; Gurzau, Eugen; Rudnai, Peter; Koppova, Kvetoslava; Févotte, Joëlle; Vahter, Marie; Leonardi, Giovanni; et al.
Abstract : Occupational studies show a high risk of lung cancer related to arsenic exposure by inhalation; however, only a few studies, and with conflicting results, previously examined a potential link between arsenic exposure at work and skin cancer. The aim of this study is to assess airborne arsenic exposures at the workplace and to quantify associations with nonmelanoma skin cancer (NMSC). The study sample consists of 618 incident cases of NMSC and 527 hospital‐based controls aged 30–79 years from Hungary, Romania and Slovakia. Exposures were evaluated by local experts using occupational histories. Information on host factors and other exposures was collected and used to adjust the associations of interest using multivariable logistic regression. The lifetime prevalence of exposure to work‐related arsenic is 23.9% for cases and 15.5% for controls. No significant association between arsenic exposure in the workplace and NMSC was detected, although an increased adjusted odd ratio was observed for participants with higher cumulative lifetime workplace exposure to arsenic in dust and fumes compared to referents [odds ratios (OR) = 1.94, 95% confidence interval (CI) = 0.76–4.95]. There is evidence for modification of the workplace arsenic–NMSC association by work‐related sunlight exposure in women, with a markedly increased adjusted OR in the presence of workplace sunlight exposure (OR = 10.22, 95% CI = 2.48–42.07). Workplace coexposure to arsenic and sunlight may thus pose an increased risk of NMSC. Abstract : What's new? While it is established that inhalation of arsenic can cause lung cancer, associations with other cancer types is less clear. Here, the authors examined a possible link of workplace exposure to the chemical element in dust and fumes with non‐melanoma skin cancer (NMSC). They find that women are at higher risk of NMSC from arsenic workplace exposure than men with a markedly increased odds ratio in the presence of additional sunlight exposure. Thus, the combined exposure to arsenic and sunlight poses a considerable risk for the development of skin cancer.